EXPLORING THE DIFFERENTIAL IMPACT OF VARIOUS USER-GENERATED CONTENT TYPES ON PURCHASE INTENTION THROUGH AWARENESS - Aquinia, Ajeng; Sutedjo, Bambang; Widyasari, Suzy; Hayuningtias, Kristina Anindita; Putra, Harmanda Berima (Management Department, Faculty of Economics and Business, Universitas Jambi, 2025)
This study investigates the role of brand awareness as a mediating variable between user generated content (UGC) and purchase intention among generation z consumers of local beauty brands. Employing a quantitative research design, data were collected from 206 respondents through online questionnaire and analyzed using partial least squares structural equation modeling (pls-sem). The measurement model shows high reliability and validity across all constructs, confirming the robustness of the data. The findings reveal that UGC has significant positive effect on both brand awareness and purchase intention, while brand awareness also positively influences purchase intention. Furthermore, the analysis confirms that brand awareness partially mediates the relationship between UGC on consumer behavior is strengthened through enhanced brand recognition and familiarity. these result highlights the crucial role of UGC in shaping consumer perception and purchase decision within the digital beauty market. The study highlights that generations Z consumers who are highly engaged with social media, respond more positively to authentic peer generated content than to traditional advertising. Therefore, local beauty brands are encouraged to utilize UGC-based marketing strategies to build stronger brand awareness and foster higher purchase intention among their target audience.